FLEXIBILITY RESTORATION OF ARTICULATIO METACARPOPHALANGEAL 1 IN CADAVER PRESERVED BY FORMALIN WITH ACETIC ACID EXPOSURE - Fitri Fitri; Marisa Riliani; Edward Syam (Fakultas Kedokteran Universitas Lambung Mangkurat, 2022)
Abstract: Cadaver rigidity due to formalin preservation often intricates students' understanding in anatomical learning. Various solutions have been trial, but there were no satisfactory results. In this study, acetic acid solution was used to restore the motion flexibility motion of small joint in the hand. Investigated the difference in motion angle of articulatio metacarpophalangeal 1 after being given acetic acid in cadaver post formalin preservation. A pair of cadaver hands conserved by formalin from the same body, were exposed to 5% acetic acid for 4 months. Angular measurements performed on flexion and extension before and after exposure. The flexibility of metacarpophalangeal joints 1 increased in the form of angular reduction in flexion movement (22.8° reduced, p<0.05) and the addition of angle to the extension movement (9.85° increased, p<0.05). Administration of acetic acid for 4 months may increase the motion flexibility of small joint like articulatio metacarpophalangeal 1 in cadaver post-formalin preservation. This result may help students to have better anatomical understanding in cadaver at anatomy laboratory. Keywords: Acetic acid; Articulatio metacarpophalangeal 1; Cadaver; Flexibility; Restoration